Alternative futures for changing landscapes : (Island Press, 2003)
Alternative Futures for Changing Landscapes presents for the first time in book form a detailed case study of one alternative futures project—an analysis of development and conservation options for the Upper San Pedro River Basin in Arizona and Sonora, Mexico. The area is internationally recognized for its high levels of biodiversity, and like many regions, it is facing increased pressures from nearby population centers, agriculture, and mining interests. Local officials and others planning for the future of the region are seeking to balance the needs of the natural environment with those of local human communities.